2021
DOI: 10.1038/s42003-021-02597-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential whole-genome doubling and homologous recombination deficiencies across breast cancer subtypes from the Taiwanese population

Abstract: Whole-genome doubling (WGD) is an early macro-evolutionary event in tumorigenesis, involving the doubling of an entire chromosome complement. However, its impact on breast cancer subtypes remains unclear. Here, we performed a comprehensive and quantitative analysis of WGD and its influence on breast cancer subtypes in patients from Taiwan and consequently highlight the genomic association between WGD and homologous recombination deficiency (HRD). A higher manifestation of WGD was reported in triple-negative br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Previous studies on molecular research in breast cancer have made significant contributions to clinical diagnosis and prognosis [ 18 ]. The heterogeneity of breast cancer subtypes has also been explained through various genomic events including large-scale somatic calls [ 19 ]. Moreover, anti-cancer peptides (ACPs), a new type of anti-cancer predictors, demonstrate the ability to inhibit the proliferation or migration of tumor cells while exhibiting a reduced propensity for inducing drug resistance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on molecular research in breast cancer have made significant contributions to clinical diagnosis and prognosis [ 18 ]. The heterogeneity of breast cancer subtypes has also been explained through various genomic events including large-scale somatic calls [ 19 ]. Moreover, anti-cancer peptides (ACPs), a new type of anti-cancer predictors, demonstrate the ability to inhibit the proliferation or migration of tumor cells while exhibiting a reduced propensity for inducing drug resistance [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…McGranahan et al explored the evolutionary importance of WGD in cancer, and showed how this can be exploited to identify novel cancer genes [ 14 ]. Chia-Hsin Wu et al discovered the distribution patterns of WGD in triple-negative BRCA patients in the Taiwanese population (BCTW) and provided insights into the impact of WGD on the timing of tumor initiation and tumor maintenance events in BRCA subtypes [ 19 ]. However, Taylor's analysis exclusively anticipated the worse overall survival across various cancer types due to genomic doubling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation